2019
DOI: 10.1186/s12889-019-6455-4
|View full text |Cite
|
Sign up to set email alerts
|

Levels and predictors of participation in integrated treatment programs for pregnant and parenting women with problematic substance use

Abstract: BackgroundWomen who are seeking services for problematic substance use are often also balancing responsibilities of motherhood. Integrated treatment programs were developed to address the diverse needs of women, by offering a holistic and comprehensive mix of services that are trauma- and violence-informed, and focus on maternal and child health promotion and the development of healthy relationships.MethodsUsing system-level administrative data from a suite of outpatient integrated programs in Ontario, Canada,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 66 publications
0
25
0
Order By: Relevance
“…These programs can be provided through various models including outreach, multi-service co-located agencies, or a network of community-based services [ 15 ]. Research in this area has shown that integrated support models can improve maternal and fetal outcomes and successfully support women to reduce alcohol use in pregnancy [ 15 , 19 , 32 , 61 , 77 ].…”
Section: Discussion and Application Of The Stigma Action Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…These programs can be provided through various models including outreach, multi-service co-located agencies, or a network of community-based services [ 15 ]. Research in this area has shown that integrated support models can improve maternal and fetal outcomes and successfully support women to reduce alcohol use in pregnancy [ 15 , 19 , 32 , 61 , 77 ].…”
Section: Discussion and Application Of The Stigma Action Frameworkmentioning
confidence: 99%
“…Moreover, as these programs offer comprehensive, wraparound services for pregnant and parenting women with substance use concerns, they are developed to match community needs and resources [ 81 ]. In Canada, researchers have evaluated both integrated substance use treatment programs in Ontario [ 20 , 74 , 77 , 81 ] as well as multi-service community-based FASD prevention programs [ 32 , 61 ].…”
Section: Discussion and Application Of The Stigma Action Frameworkmentioning
confidence: 99%
“…34 A number of studies indicated that staff understood, recognized, and accounted for the complexities of trauma for women, and sometimes children. 44 , 52 , 53 , 62 , 64 , 67 , 68 , 70 , 76 – 79 While only one study explicitly stated that staff were trained in complex trauma and trauma-informed care, 60 Tarasoff et al 75 noted that the 12 integrated treatment programs being studied embraced a trauma-informed philosophy in the ways programs were delivered as well as how staff worked with pregnant and parenting women by considering client histories and experiences of trauma in their program delivery. Hser et al 57 drew attention to how women are more likely to have coexisting complexities related to gender-specific social determinants of health when thinking about trauma.…”
Section: Resultsmentioning
confidence: 99%
“…Pregnancy is a good time to intervene as it provides a strong motivation for reducing substance use, and risk for drug abuse is substantially reduced through to the postpartum period [23]. However, engaging and retaining women in substance use interventions requires a trauma-focused and woman-centred approach that is responsive to the concerns and needs of the mother [16,21,24]. For example, Australian research has found that women who use methamphetamine in pregnancy report concerns that disclosing this may result in child removal [16,21].…”
Section: Introductionmentioning
confidence: 99%